Government-Community Collaboration in Promoting Digital Innovation among MSMEs in Makassar City - Sahid, Abdul; Malik, Sahruddin; Muliaty, Muliaty; Dwiyanti, Andi Amitya Resty (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Digital transformation has become a critical requirement for Micro, Small, and Medium Enterprises (MSMEs) to strengthen competitiveness in the digital economy. This study analyzes government–community collaboration in fostering digital innovation among MSMEs in Makassar City, Indonesia. A qualitative case study was conducted through in-depth interviews, observation, and document analysis involving MSME actors, government officials, and community leaders. The findings indicate that government programs mainly provide regulatory frameworks and resource support, while communities contribute social capital, participation, and locally adaptive practices. MSMEs increasingly use digital platforms for marketing, financial management, and customer networking. However, persistent challenges remain, including limited infrastructure, uneven digital literacy, and fragmented institutional coordination. This study highlights the relevance of collaborative governance in integrating state policies with community initiatives to accelerate MSME digital transformation. The practical implications include the need for more targeted digital literacy training, the establishment of community-based innovation hubs, and long-term partnership models to ensure sustainable digital ecosystems. Theoretically, the study contributes to discussions on governance and digital innovation in developing economies by contextualizing collaborative practices within a mid-sized Indonesian city.